HJURP antagonizes CENP-A mislocalization driven by the H3.3 chaperones HIRA and DAXX - Nye, Jonathan (PLoS One, 2018)
The centromere specific histone H3 variant CENP-A/CENH3 specifies where the kinetochore is formed in most eukaryotes. Despite tight regulation of CENP-A levels in normal cells, overexpression of CENP-A is a feature shared by various types of solid tumors and results in its mislocalization to non-centromeric DNA. How CENP-A is assembled ectopically and the consequences of this mislocalization remain topics of high interest. Here, we report that in human colon cancer cells, the H3.3 chaperones HIRA and DAXX promote ectopic CENP-A deposition. Moreover, the correct balance between levels of the centromeric chaperone HJURP and CENP-A is essential to preclude ectopic assembly by H3.3 chaperones. In addition, we find that ectopic localization can recruit kinetochore components, and correlates with mitotic defects and DNA damage in G1 phase. Finally, CENP-A occupancy at the 8q24 locus is also correlated with amplification and overexpression of the MYC gene within that locus. Overall, these data provide insights into the causes and consequences of histone variant mislocalization in human cancer cells.